Penerapan Teknologi Informasi dalam Manajemen Mutu Terpadu Pendidikan Islam di MIS Ashhabul Qur'an Bukittinggi - Fitriani, Yenni; Sesmiarni, Zulfani; Ramlan, Muhammad (Arfannur: Journal of Islamic Education, 2025)
This study aims to analyze the application of information technology in integrated quality management of Islamic education at MIS Ashhabul Qur'an Bukittinggi. Using descriptive qualitative research methods and a case study approach, this research explores how information technology is integrated in various aspects of educational management, such as student data management, the learning process, and communication between schools and parents. Data collection techniques were conducted through in-depth interviews, direct observation and documentation studies involving the school, teachers, administrative staff and parents. The results showed that the application of information technology at MIS Ashhabul Qur'an Bukittinggi has brought positive impacts in improving administrative efficiency, enriching the learning process, and facilitating communication between the school and parents. However, challenges such as limited infrastructure, teachers' readiness to operate technology and resistance to change are still obstacles that need to be overcome. This study recommends the importance of continuous training for teachers, updating technology devices and improving infrastructure facilities to ensure a more optimal implementation of technology. The application of information technology in this school can serve as an example for other Islamic education institutions to improve the quality of education management in order to achieve better education quality.